2009
DOI: 10.1016/j.jbtep.2009.06.001
|View full text |Cite
|
Sign up to set email alerts
|

What you believe is what you want: Modeling PTSD-related treatment preferences for sertraline or prolonged exposure

Abstract: Despite the known efficacy of various psychotherapies and pharmacotherapies for posttraumatic stress disorder (PTSD), we know little about what factors predict treatment preference. In the present study, we first developed exploratory path models of treatment preference for a psychotherapy or pharmacotherapy (n = 273) and then conducted confirmatory analyses of these models in a second sample (n = 324) and in a third generalization sample of trauma-exposed women (n = 105). We examined demographic and psychopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 46 publications
2
49
2
Order By: Relevance
“…It was hypothesized that CBT would be considered as more acceptable than pharmacotherapy. The results support this hypothesis and are consistent with those found in young (Deacon & Abramowitz, 2005;Zoellner et al, 2009) and older adults (Mohlman, 2012). The results concerning CBT and CBT-GSH are mixed.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It was hypothesized that CBT would be considered as more acceptable than pharmacotherapy. The results support this hypothesis and are consistent with those found in young (Deacon & Abramowitz, 2005;Zoellner et al, 2009) and older adults (Mohlman, 2012). The results concerning CBT and CBT-GSH are mixed.…”
Section: Discussionsupporting
confidence: 88%
“…Both medication and CBT were generally perceived as acceptable, believable, and effective. Similarly, Zoellner, Feeny, and Bittinger (2009) found that prolonged exposure is preferred over sertraline for posttraumatic stress disorder across adult samples of undergraduate students and trauma-exposed women. This research has also known that treatment history (Deacon & Abramowitz, 2005) and severity of psychopathology (Zoellner et al, 2009) both influence the perception of anxiety treatments.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Despite the efficacy of TIDES for older veterans with depression, collaborative care models may need to be modified to be most effective in OEF/OIF veterans. For example, younger and minority combat veterans with anxiety disorders may be reluctant to accept medication and may instead prefer psychotherapy 50,[52][53][54] . Evidence-based psychotherapy for PTSD and other anxiety disorders is typically delivered in specialty mental health settings, but a recent study of OEF/OIF veterans with new PTSD diagnoses in VA healthcare showed that veterans' failed to attend an adequate number of specialty mental health visits required for evidence-based PTSD treatment 55 .…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of literature in support of the notion that outcomes are improved when the PTSD treatment received matches the client's preference for treatment, i.e., the treatment you think is best for you is best for you (Le, Doctor, Zoellner, & Feeney, 2014;Zoellner, Feeny, & Bittinger, 2009). The Department of Veterans Affairs has wisely built into their specialty clinic intake process an orientation group received very positively by veterans that explains psychotherapy and pharmacotherapy treatment options for PTSD (Schumm, Walter, Bartone, & Chard, 2015).…”
Section: Client Preference For Type Of Treatmentmentioning
confidence: 99%